Invited Commentary: Broadening the Evidence for Adolescent Sexual and Reproductive Health and Education in the United States. - Schalet, Amy; Santelli, John; Russell, Stephen; Halpern, Carolyn; Miller, Sarah; Pickering, Sarah; Goldberg, Shoshana; Hoenig, Jennifer (Journal of Youth & Adolescence, 2014)
Scientific research has made major contributions to adolescent health by providing insights into factors that influence it and by defining ways to improve it. However, US adolescent sexual and reproductive health policies-particularly sexuality health education policies and programs-have not benefited from the full scope of scientific understanding. From 1998 to 2009, federal funding for sexuality education focused almost exclusively on ineffective and scientifically inaccurate abstinence-only-until-marriage (AOUM) programs. Since 2010, the largest source of federal funding for sexual health education has been the 'tier 1' funding of the Office of Adolescent Health's Teen Pregnancy Prevention Initiative. To be eligible for such funds, public and private entities must choose from a list of 35 programs that have been designated as 'evidence-based' interventions (EBIs), determined based on their effectiveness at preventing teen pregnancies, reducing sexually transmitted infections, or reducing rates of sexual risk behaviors (i.e., sexual activity, contraceptive use, or number of partners). Although the transition from primarily AOUM to EBI is important progress, this definition of evidence is narrow and ignores factors known to play key roles in adolescent sexual and reproductive health. Important bodies of evidence are not treated as part of the essential evidence base, including research on lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ) youth; gender; and economic inequalities and health. These bodies of evidence underscore the need for sexual health education to approach adolescent sexuality holistically, to be inclusive of all youth, and to address and mitigate the impact of structural inequities. We provide recommendations to improve US sexual health education and to strengthen the translation of science into programs and policy.